2000
DOI: 10.1007/s002770000250
|View full text |Cite
|
Sign up to set email alerts
|

Severe hemolytic anemia and excessive leukocytosis masking mycoplasma pneumonia

Abstract: The formation of cold agglutinins is frequently observed during Mycoplasma pneumoniae infections. Nevertheless, severe hemolysis is exceptional. We report a case of life-threatening hemolytic anemia caused by M. pneumoniae. As the leucocyte count was excessively elevated, the differential diagnosis primarily comprised hematological malignancies. The presence of cold agglutinins indicated the correct diagnosis, which was confirmed by highly elevated levels of both IgG and IgM antibodies to M. pneumoniae and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 9 publications
0
29
0
8
Order By: Relevance
“…The coincidence of elevated serum levels of lactate dehydrogenase and bilirubin with low levels of haptoglobin is common in hemolytic anemia caused by cold agglutinins [5]. Our patient showed both features of extra-and intravascular hemolysis.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…The coincidence of elevated serum levels of lactate dehydrogenase and bilirubin with low levels of haptoglobin is common in hemolytic anemia caused by cold agglutinins [5]. Our patient showed both features of extra-and intravascular hemolysis.…”
Section: Discussionmentioning
confidence: 49%
“…An increase in cold agglutinin titers is frequently observed during M. pneumoniae infection; it has been reported that 50%-60% of these patients had cold agglutinins [9,10], which appear one week after the onset of the illness and decline toward undetectable levels after two to six weeks [5]. Cold agglutinins appear to be more specific for I antigen of the red blood cell surface and often result in mild, subclinical hemolysis and mild reticulocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations